Presbyterianism, Secularization, and Scottish Politics After the Revolution Of 1688–1690 - Raffe, Alasdair (The historical journal, 2010)
This article assesses the significance of Presbyterian ideas of church government in Scottish politics after the revolution of 1688–90. While recent historians have revised our understanding of Scottish politics in this period, they have mostly overlooked debates concerning religious authority. The article focuses on what contemporaries called the ‘intrinsic right’ of the church: its claim to independent authority in spiritual matters and ecclesiastical administration. The religious settlement of 1690 gave control of the kirk to clergy who endorsed divine right Presbyterianism, believed in the binding force of the National Covenant (1638) and the Solemn League and Covenant (1643), and sought to uphold the intrinsic right. An ambiguous legal situation, the criticisms of episcopalian clergy and politicians, and the crown's religious policies helped to make the Presbyterians' ecclesiological claims a source of instability in Scottish politics. Meetings of the general assembly and, after 1707, the appointment of national fast and thanksgiving days were particularly likely to spark controversy. More broadly, the article questions two narratives of secularization assumed by many previous scholars. It argues that Scottish politics was not differentiated from religious controversy in this period, and that historians have exaggerated the pace of liberalization in Scottish Presbyterian thought.